Penerapan Model Pembelajaran Inkuiri Untuk Meningkatkan Hasil Belajar Ipa Siswa Kelas V SD Inpres 6/75 Ta’ Kecamatan Tanete Riattang Kabupaten Bone - Rahmawati Patta (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2017)
The purpose research is of this study is for decribe application of inquiry learning model can improve science learning outcomes of fifth gradestudents of  SD inpres 6/75  Ta’ sub-district Tanete Riattang district Bone. This classroom action research is recyled using a descriptive qualitative approach. Each cycle consists of four stages including planning, execution, observation and reflection. The focus of this research is application of inquiry learning model and science learning outcomes. Subject of this research is teacher and of fifth gradestudents of  SD inpres 6/75  Ta’ sub-district Tanete Riattang district Bone. The data collection technique is test, observation and documentation with qualitative data analysis techniques that is reduce data, presents data and draw a conclusion. Research result shows improvement in student learning outcomes from cycle I with enough category and increased into a good category in cycle II. The conclusion of this study is to use application of inquiry learning model can improve science learning outcomes of fifth gradestudents of  SD inpres 6/75 Ta’ sub-district Tanete Riattang district Bone.